A dose-response study of HOE 498, a new non-sulphydryl converting enzyme inhibitor, on blood pressure, pulse rate and the renin-angiotensin-aldosterone system in normal man. - Manhem, P J (1985)
The effect of different oral doses of HOE 498, a new non-sulphydryl containing converting enzyme inhibitor, was investigated in a double-blind, placebo-controlled study in normotensive volunteers. Dose-related reductions in serum converting enzyme activity, plasma angiotensin II and aldosterone were seen, greater at 4 h than at 12 h after drug ingestion. Converse dose-related increases in blood angiotensin I and plasma active renin concentration occurred. Falls of angiotensin II were as great with 20 mg as with 50 mg of HOE 498, although the effect was more prolonged with 50 mg. The reductions in concentrations of plasma angiotensin II and serum converting enzyme activity and the increases in plasma renin concentration were correlated with the concentration of HOE 498 - diacid in plasma. Dose-related falls in both supine and erect blood pressure were maximal 2-3.5 h after dosing. Pulse rate increased marginally but insignificantly in the supine; slightly and significantly in the upright position, concomitantly with the blood pressure reduction at all doses of active drug. We conclude that effects of single doses of HOE 498 on the renin-angiotensin system are maximal within 4 h, but are still apparent after 24 h. Thus it is likely that once daily administration will be adequate for treatment of high blood pressure in patients.